Evaluation of accuracy of transvaginal ultrasound in lower uterine segment caesarean scar integrity and histomorphometric analysis of scar tissue: a prospective study - Salim, Simmi; Parameswaran, Biju; Balakrishnan, Deepthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Caesarean section is the most common method of delivery in the present conditions. The present study conducted to evaluate the accuracy of transvaginal ultrasound in lower uterine segment caesarean scar integrity and histomorphometric analysis of scar tissue. Methods: The study was conducted in the department of OBG, SUT academy of medical sciences, Vattapara, Trivandrum, Kerala. Based on the inclusion and exclusion criteria a total of 144 patients were included in the study. All patients explained study procedure and informed consent was obtained. They were subjected to transvaginal ultrasound examination after that small piece of scar tissue was taken and used for histomorphic analysis. The data was analysed by SPSS (16.0) version used. Results: In group-I 31.11% showed 40 and above fibrosis and group-II 85.0% had fibrosis 40 and above. 8 in group-I showed 0-19% of fibrosis and 17 in group-II. 0-19% whereas vicryl had a range of 0-40% and above and the rate of fibrosis compared to transvaginal sonography not showed significant difference. Conclusions: Histomorphological analysis of scar tissue gave accurate results and it was similar to transvaginal ultrasonography results.